The Translation of John Stuart Mill's Considerations on Representative Government (1861) in the Spanish-speaking World: A Case Study. - Ramírez-Arlandi, Juan (My University, 2024)
This article examines the sustained dissemination of John Stuart Mill’s Considerations On Representative Government (1861) through Spanish-language translations on both sides of the Atlantic, from the initial Chilean translation, published in 1865, to the present day. Adopting methodological assumptions from the field of Post-Translation Studies, contributions from Translator Studies on translators’ biographies, Lepinette’s model of the history of translation integrating the sociocultural and the descriptive-contrastive approaches, and Toury’s norm-based approach within Descriptive Translation Studies, this case study examines the description of translators’ lives and works, paratexts, French mediating translations, editors, and publishers in order to precisely determine both the initial and the preliminary norms these versions originally adhered to. Furthermore, a detailed analysis of the operational norms —particularly those concerning the annotations made by translators and the author— provides insights not only into the translation theory underlying the translated texts but also into the intertextual relationships between the source text(s) and the translated versions.
Keywords: Mill, John Stuart - Traducciones españolas; Traducción - Historia; History of translation; John Stuart Mill; Translation of essayistic texts; Translation norms; Paratexts